2001
DOI: 10.1258/1357633011936435
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and cost analysis of patient referral by videoconferencing in orthopaedics

Abstract: The clinical effectiveness and costs of videoconferencing in orthopaedics between primary and secondary care were examined in an eight-month prospective, comparative study. The general surgery outpatient clinics of two Finnish district hospitals were compared: Peijas Hospital, with telemedicine, and Hyvinkää Hospital, without it. The three study primary-care centres referred a total of 419 adult patients to the outpatient clinics. The population-based number of referrals to Peijas Hospital was similar to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 15 publications
5
69
1
Order By: Relevance
“…Others have investigated remote orthopaedic consultations by various means (videoconference [18][19][20][21][22] , Skype 23 , or teleconference 24 ) and reported cost-savings and similar clinical outcomes compared with in-clinic assessments. Although those alternative methods may achieve savings in some circumstances, the webbased system for routine arthroplasty follow-up provides greater flexibility to complete the assessment at a time and location *The values are given as the mean and the standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Others have investigated remote orthopaedic consultations by various means (videoconference [18][19][20][21][22] , Skype 23 , or teleconference 24 ) and reported cost-savings and similar clinical outcomes compared with in-clinic assessments. Although those alternative methods may achieve savings in some circumstances, the webbased system for routine arthroplasty follow-up provides greater flexibility to complete the assessment at a time and location *The values are given as the mean and the standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…8 An eight-month prospective study compared orthopaedic surgery outpatient clinics with telemedicine to those clinics without telemedicine (n ¼ 419 patients). 4 The findings demonstrated that the diagnoses were revised to a similar degree after orthopaedic surgery teleconsultations (12%) and after face-to-face clinic visits (16%), when compared with the diagnoses established by the general practitioners. Results from an experimental study (n ¼ 108 patients with 123 acute fractures) indicated that additional information provided by viewing electronically transmitted images of radiographs changed the acute 15 A six-month pilot teleconsultative project was designed to examine the effectiveness of telemedicine on the clinical decision-making process for patients with urolithiasis (urinary calculi).…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have been performed to assess the effect of telemedicine on changes in the patient's diagnosis and treatment plan. [2][3][4][7][8][9][10][11][12][13] The University of Arkansas for Medical Sciences (UAMS) began a project in 1995 to provide telemedicine for a poor, under-served, rural population in the East Arkansas Delta. The target area was seven counties in Arkansas.…”
Section: Introductionmentioning
confidence: 99%
“…32 Accordingly, some surgeons have removed "hands-on" assessments, conducting perioperative visits using secure two-way interactive video. [33][34][35][36][37] Still others have eliminated both "hands-on" and visual assessments, using telephone to follow-up adults after laparoscopic cholecystectomy and inguinal hernia repair as well as a variety of minor pediatric general surgical procedures. [38][39][40] Both video and telephone-based care are limited in that they must be performed in a synchronous fashion, with both patient and surgeon available concurrently to participate in follow-up.…”
Section: Discussionmentioning
confidence: 99%